2019
DOI: 10.18632/aging.101856
|View full text |Cite
|
Sign up to set email alerts
|

Gene signatures and prognostic values of m6A regulators in clear cell renal cell carcinoma – a retrospective study using TCGA database

Abstract: m6A is the most common form of mRNA modification. However, little is known about its role in clear cell renal cell carcinoma (ccRCC). This study aims to identify gene signatures and prognostic values of m6A regulators in ccRCC. In this study, a total of 528 ccRCC patients from TCGA database with sequencing and CNV data were included. Survival analysis was performed using log-rank tests and Cox regression model. The association between alteration of m6A regulators and clinicopathological characteristics was exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
162
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(168 citation statements)
references
References 38 publications
(40 reference statements)
6
162
0
Order By: Relevance
“…There were 13 m 6 A RNA methylation genes brought into the study, namely, METTL3, METTL14, WTAP, KIAA1429, RBM15, ZC3H13, YTHDC1, YTHDC2, YTHDF1, YTHDF2, HNRNPC, FTO, and ALKBH5 [45,46]. We investigated their role in diagnosis, progression, and prognosis of lung adenocarcinoma of both training and validation cohort.…”
Section: Selection Of Investigative Genesmentioning
confidence: 99%
“…There were 13 m 6 A RNA methylation genes brought into the study, namely, METTL3, METTL14, WTAP, KIAA1429, RBM15, ZC3H13, YTHDC1, YTHDC2, YTHDF1, YTHDF2, HNRNPC, FTO, and ALKBH5 [45,46]. We investigated their role in diagnosis, progression, and prognosis of lung adenocarcinoma of both training and validation cohort.…”
Section: Selection Of Investigative Genesmentioning
confidence: 99%
“…METTL3 has been demonstrated to be dysregulated in diverse human malignancies and involved in many aspects of carcinogenesis. Zhou et al showed that METTL3 and METTL14 exhibited higher expression in clear cell renal cell carcinoma than in normal samples and that patients with deletion of METTL3 had poorer overall survival (OS) and disease-free survival (DFS) (22). Liu et al revealed that the proliferation, viability, and migration of gastric cancer cells with METTL3 silencing in vitro were significantly inhibited compared with those of control cells (23).…”
Section: Introductionmentioning
confidence: 99%
“…The different expression of these m6A regulators may eventually lead to the various of survival outcomes. [21] Among the m6A regulators, previous studies indicated that the eraser ALKBH5 can induce breast cancer stem cell and glioblastoma stem-like cell proliferation and tumor initiation, [22] the writers METTL3 and METTL14 were reported to enhance glioblastoma growth and suppress Liver cancer metastasis, [23][24][25] the reader YTHDF1 and YTHDF2 induce cancer cell proliferation in colon cancer and lung oncogenic effects. [26,27] These ndings manifested that high or low expression of speci c m6A regulators are related to misregulation of RNAs in tumors, and the same m6A regulator may take different functions in various tumors.…”
Section: Discussionmentioning
confidence: 99%